D. J. Dwyer. People and housing in the Third World cities. Londres : Longman, 1979 - Garza Villarreal, Gustavo (Estudios Demográficos y Urbanos, 1979)
D, J. DWYER, People and Housing in the Third World Cities, Londres, Longman, 1979.